PELATIHAN BAHASA INGGRIS DAN PEMBUATAN MINUMAN TRADISIONAL BAGI MASYARAKAT DESA MANUKAYA, KABUPATEN GIANYAR DALAM MENDUKUNG PERJAMUAN INTERNASIONAL DI ISTANA PRESIDEN TAMPAKSIRING - Febrianto, I Gusti Agung; Rusdianata, I Ketut; Saputra, I Nyoman Gede Agus Jaya; Widuri, Setyowati Ayu; Muliana, I Wayan; Juniari, Ni Kadek Eni; Budiani, Ni Putu Ariesta; Pranadewi, Putu Mira Astuti; Sudiparwati, Putu Ayu; Arcana, I Nyoman; Rinala, I Nyoman; Massenga, Lidjah Magdalena; Pastini, I Wayan (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This community service activity carried out by the Bali Tourism Polytechnic TAH Study Program is a 2 day training activity, which is a continuation of the previous PKM TAH Study Program which was held in May 2024 in Manukaya Village, Gianyar Regency. This PKM activity focuses on English training for restaurants and making traditional drinks which will be provided to the community in Manukaya Village. The target of this PKM activity is so that people involved in tourism have sufficient knowledge to start a restaurant business and are able to provide food and drink products for tourists visiting Manukaya Village. Through this training activity, it is hoped that the people of Manukaya Village will open their minds about the world of Food and Beverages and can take advantage of this opportunity as a new business opportunity with a total of 30 participants consisting of community members who own simple accommodation and agro-tourism in Manukaya Village, members of the Pokdarwis who involved in the hospitality sector as well as the Manukaya Village PKK which is often involved in banquet activities at the Tampaksiring Presidential Palace. The output of this activity is to improve the community's ability to communicate in English, especially when providing services to tourists, to create a traditional drink using local ingredients produced in Manukaya Village, as well as to increase the community's ability to provide food and drink services